Research on Medication Rules of Chronic Gastritis and Allergic Rhinitis Based on the Complex System Entropy Clustering Method - Liu, Renquan; Zhao, Yuhao; Shi, Chenghe; Chen, Guoyong (IntechOpen, 2012)
None